ECONOMIC IMPACT OF THE ONE BELT ONE ROAD INITIATIVE ON SOUTHEAST ASIAN COUNTRIES - Zubayda Murotalieva (Modern American Journals, 2025)
This paper examines the economic impact of the Belt and Road Initiative (OBOR) on 4 selected Southeast Asian economies, using both quantitative and qualitative methods. The benefits of the OBOR project are evaluated by considering important economic variables including GDP growth, trade, foreign direct investment (FDI), human development index (HDI), and government debt. To boost the significance of the study, regression analysis is done and descriptive statistics are explained in detail. The results show that there are significant differences in economic results across states under observation, which may be affected by other factors such as geographic location, policy differences, and infrastructural connection. Several policy recommendations by researchers highlight the importance of strategic planning, infrastructure investment, and sustainable development to increase the advantages of participating in the OBOR initiative and fostering sustainable growth in the area. The study also emphasizes the necessity of ongoing investigation and cooperation to track the changing effects of OBOR and provide information for evidence-based policy choices.
Keywords: OBOR, economic growth, government debt